Microbiological assessment of grilled chicken isaw from selected sources in Iloilo City - Salmorin, Ma. Rhoda Socorro Caspillo
Grilled chicken isaw were obtained from five different vendors (identified as A, B, C, D, and E) in Iloilo City.